Vacuum-arc superhard TIN coatings and usage of them for tool hardening - Андреев, Анатолий Афанасьевич; Столбовой, Вячеслав Александрович; Сердюк, Ирина Витальевна (Eastern-European Journal of Enterprise Technologies, 2012)
Vacuum-arc TIN coutings on high-speed steel R6M5 substrate with the use of method of ionic implantation (PBIID) in the range of potentials of substrate -40…-400 V and pressures of nitrogen 0,01…0,66 Pa have hardness 40…65 GPa. These coutings provide high working capacity of tools